Associations among professional quality of life dimensions, burnout, nursing practice environment, and turnover intention in newly graduated nurses. Issue 2 (17th March 2022) - Gong, Shu; Li, Jin; Tang, Xiangdong; Cao, Xiaoyi
Abstract: Background: Professional quality of life affects nurses' well‐being and the quality of care. However, little attention is paid to the relationships among professional quality of life dimensions, burnout, nursing practice environment, and intention to leave this job in newly graduated nurses. Aims: To assess the levels of professional quality of life dimensions and turnover intention, to examine the predictors for turnover intention, and to explore the mediating roles of professional quality of life dimensions on the associations between these predictors and turnover intention in Chinese newly graduated nurses. Methods: This was a cross‐sectional study with 315 newly graduated nurses selected from five tertiary hospitals and five secondary hospitals in Sichuan province, China. Multiple regression analysis was used to examine the effects of demographic characteristics and work‐related factors on intention to leave this job. Structural equation modeling technique was performed to explore the mediating effect of each domain of professional quality of life on the relationships between the predictors and turnover intention. Results: The prevalence of average levels of burnout, secondary traumatic stress, and compassion satisfaction was 43.2%, 57.1%, and 81.3%, respectively. Moreover, 43.8% and 0.6% of the participants reported high and exceptionally high intention to leave this job. Nursing practice environment, social support, and empathy indirectly and significantly affected turnover intention via the mediating roles of burnout and compassion satisfaction, respectively. However, no significant mediating effect of secondary traumatic stress was found between these predictors and turnover intention. Linking Evidence to Action: Perceptions of greater nursing practice environment, social support, and empathy result in lower turnover intention via reducing burnout and facilitating compassion satisfaction. Strategies such as developing a supportive work and family environment, and cultivating empathic capacity can be effective methods to mitigate against intention to leave this job in newly graduated nurses.